2021
DOI: 10.3389/fneur.2021.547655
|View full text |Cite
|
Sign up to set email alerts
|

Localizing Clinical Patterns of Blast Traumatic Brain Injury Through Computational Modeling and Simulation

Abstract: Blast traumatic brain injury is ubiquitous in modern military conflict with significant morbidity and mortality. Yet the mechanism by which blast overpressure waves cause specific intracranial injury in humans remains unclear. Reviewing of both the clinical experience of neurointensivists and neurosurgeons who treated service members exposed to blast have revealed a pattern of injury to cerebral blood vessels, manifested as subarachnoid hemorrhage, pseudoaneurysm, and early diffuse cerebral edema. Additionally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…To the authors knowledge, this is the first experimental data localizing intra-sulcal cavitation and capturing the resultant response of model gyri / sulci during head trauma. Previous studies ( 29 , 30 , 34 , 35 ) also observed cavitation as a result of loading and recent computational results also suggest intrasulcal cavitation could occur during blast exposure ( 46 ). However, the previously reported experiments supporting the cavitation mechanism either incorporated a neck-model directly, or observed the cavitation after the onset of rotational or angular acceleration.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…To the authors knowledge, this is the first experimental data localizing intra-sulcal cavitation and capturing the resultant response of model gyri / sulci during head trauma. Previous studies ( 29 , 30 , 34 , 35 ) also observed cavitation as a result of loading and recent computational results also suggest intrasulcal cavitation could occur during blast exposure ( 46 ). However, the previously reported experiments supporting the cavitation mechanism either incorporated a neck-model directly, or observed the cavitation after the onset of rotational or angular acceleration.…”
Section: Discussionmentioning
confidence: 78%
“…Arterial vasculature resides in the same subarachnoid space where cavitation is hypothesized to exist and thus could be directly injured from a cavitation event. The presence of vascular structures within the CSF space further confines fluid and this confinement could increase likelihood of cavitation—as has been suggested in computational simulations of blast injury ( 46 ). However, the mechanisms of cavitation within confined fluid spaces remain complex and will require dedicated studies.…”
Section: Discussionmentioning
confidence: 92%
“…1 b and c. This model demonstrates the overall size characteristics of the human brain with the interactions of the sulci and gyri (folds and grooves). This phantom was reviewed and verified by a board-certified neurologist who confirmed the phenomenology similarity with a real brain 18 . The computational model was able to show higher strains within the brain interfaces and folds, supporting the hypothesis that blast TBI causes more damage in sulci and gyri 18 .…”
Section: Introductionmentioning
confidence: 99%
“…This phantom was reviewed and verified by a board-certified neurologist who confirmed the phenomenology similarity with a real brain 18 . The computational model was able to show higher strains within the brain interfaces and folds, supporting the hypothesis that blast TBI causes more damage in sulci and gyri 18 . To build a brain phantom suitable for experiments, Wermer et al studied different materials to determine the best biofidelic representative of the brain matter.…”
Section: Introductionmentioning
confidence: 99%
“… 7 , 14 , 15 The potential injury to neurons, glia, and cerebrovasculature may be heterogeneous with respect to anatomic distribution, cell type, and severity. 16 This pathophysiological heterogeneity may explain the broad range of mutually exacerbating symptoms experienced by highly exposed military personnel. 17–21 …”
Section: Introductionmentioning
confidence: 99%